2011
DOI: 10.1167/iovs.09-4866
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Recombinant Myocilin with the Matricellular Protein SPARC: Functional Implications

Abstract: Recombinant myocilin and SPARC interact through their C-terminal domains. The data suggest that the proteolytic processing of myocilin modulates this interaction as well as the interactions of myocilin with other extracellular matrix and matricellular proteins, further supporting a functional role for this proteolytic cleavage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 45 publications
1
38
0
Order By: Relevance
“…217 It was originally perceived as a potential key player in regulation of ECM turnover within the TM and JCT, in part due to its notable C-terminal interaction with myocilin, 218 something it shares in common with SPARC. 94 In human 293-T cells, Li et al showed that hevin interacts with myocilin and that myocilin causes accumulation of hevin. 218 Of note, patients with myocilin-associated POAGwhich demonstrates an over 90% penetrance in heterozygous individuals-generally present with high IOP.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…217 It was originally perceived as a potential key player in regulation of ECM turnover within the TM and JCT, in part due to its notable C-terminal interaction with myocilin, 218 something it shares in common with SPARC. 94 In human 293-T cells, Li et al showed that hevin interacts with myocilin and that myocilin causes accumulation of hevin. 218 Of note, patients with myocilin-associated POAGwhich demonstrates an over 90% penetrance in heterozygous individuals-generally present with high IOP.…”
Section: Figmentioning
confidence: 99%
“…91,92 The gene that encodes myocilin was one of the first to be linked to POAG, 93 and myocilin's C-terminal domain interacts with that of SPARC. 94 Previous studies have suggested that most disease-causing myocilin gene mutations interfere with myocilin protein production 93 or proper folding and secretion, [95][96][97] giving rise to an ''intracellular sequestration'' model of disease pathogenesis. However, one report found that approximately twenty percent of diseasecausing mutants yielded protein products that were still successfully secreted and recovered from culture media.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular Myocilin Enhances Osteogenic Differentiation of MSCs-Myocilin is a secreted glycoprotein that may interact with frizzled receptors on the cell surface (14) and with extracellular proteins (25,26). Because the expression of myocilin was increased in MSCs differentiating into osteoblasts, we tested whether treatment with extracellular myocilin might affect MSC osteogenesis.…”
Section: Myocilin Is Expressed In Mouse Rat and Human Mscs-mentioning
confidence: 99%
“…4,19 Although the exact role of wild type (WT) MYOC is not completely understood, myocilin appears to be released into the ECM as exosomes and may have an extracellular function. 20–22 Wild-type myocilin has been shown to interact with fibronectin in vitro. 23 In addition, myocilin appears to colocalize with fibronectin, collagen type IV, and laminin in cultured TM cells treated with dexamethasone (Dex).…”
mentioning
confidence: 99%